Imperatorin ameliorates pulmonary fibrosis via GDF15 expression - Tsai, Cheng-Fang; Chen, Yen-Chang; Li, Ya-Zhen; Wu, Chen-Teng; Chang, Pei-Chun; Yeh, Wei-Lan (Frontiers in Pharmacology, 2023)
Background: Pulmonary fibrosis features in damaged pulmonary structure or over-produced extracellular matrix and impaired lung function, leading to respiratory failure and eventually death. Fibrotic lungs are characterized by the secretion of pro-fibrotic factors, transformation of fibroblasts to myofibroblasts, and accumulation of matrix proteins. Hypothesis/purpose: Imperatorin shows anti-inflammatory effects on alveolar macrophages against acute lung injury. We attempt to evaluate the properties of imperatorin on the basis of fibroblasts. Methods: In in vitro, zymosan was introduced to provoke pro-fibrotic responses in NIH/3T3 or MRC-5 pulmonary fibroblasts. Imperatorin was given for examining its effects against fibrosis. The mice were stimulated by bleomycin, and imperatorin was administered to evaluate the prophylactic potential in vivo. Results: The upregulated expression of connective tissue growth factor (CTGF), α-smooth muscle actin (α-SMA), and collagen protein due to zymosan introduction was decreased by imperatorin in fibroblasts. Zymosan induced the activity of transglutaminase 2 (TGase2) and lysyl oxidase (LOX), which was also inhibited by the administration of imperatorin. Imperatorin alone enhanced sirtuin 1 (SIRT1) activity and growth differentiation factor 15 (GDF15) secretion in fibroblasts via LKB1/AMPK/CREB pathways. In addition, GDF15 exerted a beneficial effect by reducing the protein expression of CTGF, α-SMA, and collagen and the activities of TGase and LOX. Moreover, orally administered imperatorin showed prophylactic effects on bleomycin-induced pulmonary fibrosis in mice. Conclusion: Imperatorin reduces fibrotic marker expression in fibroblasts and also increases GDF15 secretion via the LKB1/AMPK/CREB pathway, attenuating pro-fibrotic responses in vitro. Imperatorin also alleviates pulmonary fibrosis induced by bleomycin in vivo.